PENENTUAN NILAI SPF (SUN PROTECTION FACTOR) EKSTRAK ETANOL BUNGA PULUTAN ( Urena lobata L.): PENENTUAN NILAI SPF (SUN PROTECTION FACTOR) EKSTRAK ETANOL BUNGA PULUTAN ( Urena lobata L.) - Masykuroh, Athiah; Dian Kartika Sari; Husnani (Akademi Farmasi Yarsi Pontianak, 2024)
Urena lobata L. are known contains secondary metabolites of alkaloids, terpenoids, phenols, flavonoids, saponins and tannins and have very strong antioxidant activity. This causes the ethanolic extract of Urena lobata L. flowers have the ability to ward off free radicals and UV radiation. This research aims was to find out whether the ethanolic extract of urena lobata L. flowers has Sun Protection Factor (SPF) activity and how much value it has. Determination of the SPF value was carried out by measuring the absorbance of the ethanolic extract of Urena lobata L. flowers with concentration of 4000 ppm using UV-Vis Spectrophotometry at 290-320 nm wavelength. The results showed that the ethanolic extract of Urena lobata L. flowers has SPF activity. The average SPF value obtained was 2.43, which is included in the weak category.